Domestic Instability, Global Order and Nepali Foreign Policy - Subedi, Hem Raj (Journal of Foreign Affairs, 2023)
The foreign policy of Nepal is not hindered by a lack of understanding of its principles but rather by the complex relationship between domestic and external factors. In an ideal scenario, Nepal would define its interests clearly and engage with foreign powers in a rational manner to achieve its objectives. For example, if Nepal recognizes the need for foreign aid to improve its infrastructure, it would approach relevant external powers. Before doing so, Nepal would conduct thorough due diligence to assess the benefits of the project and ensure its economic viability. The entire process would be conducted transparently, allowing external actors to receive a similar deal and comprehend Nepal’s reasoning. This approach would help Nepal maintain control over foreign influence. Unfortunately, Nepali leaders and policymakers have often treated foreign powers as tools to retain or gain domestic power, and at times, to serve their personal interests. This reliance on foreign powers makes them more dependent and impairs their ability to make decisions in the best interest of the nation. Therefore, it is crucial for Nepali policymakers to take matters into their own hands. The first step is to strengthen domestic unity concerning foreign and security policies, which may require leaders to sacrifice their personal or party interests. The future of Nepali foreign policy hinges on whether these leaders are willing to make such sacrifices.